Experience of Using PBL and Gamification as an Active Methodology in Time of Pandemic in Ecuador - Gómez, Juan Manuel (2023)
During the COVID 19 pandemic, the use of innovative and attractive strategies within educational environments has been demonstrated, where teaching is focused on the student, in the development of skills. These strategies conceive learning as a constructive and motivating process. To do this, a topic that generates great interest in the current educational scenario was analyzed: the active methodologies applied within the current situation experienced by the pandemic; which is eminent because through its use it is possible to continue with the teaching/learning process between teacher and student in difficult times such as those currently experienced by society in general. The objective is to know the experiences of teachers in the application of PBL and Gamification as strategies of active methodologies in the teaching process. The methodology is qualitative approach. The sample consisted of 15 teachers from the Sierra del Ecuador educational system. The survey technique was applied. In conclusion, it has been confirmed that the application of active methodologies encourages students to learn, in a practical way, useful and concrete knowledge that they will usually find in their daily context and curiosity about learning is rewarded.